Education Thought Imam Zarnuji and Paulo Freire: An Synthesis Analysis - Moch Tolchah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
Keywords: Synthesis Analysis, Zarnuji education thinking, Paulo Freire education thinkingThis research focuses on several issues as follows: first, how is the concept of education according to Imam Zarnuji; second, what is the concept of education according to Paulo Freire; Third, how is the comparison between Imam Zarnuji and Paulo Freire's education, and can both be synthesized towards Qur'ani educationThe concept of education offered by Zarnuji and Freire can be said as a representation of Islamic and Western education, both of which have sides of equality and there are sides of difference; there are strong sides and weak sides. There should be an effort to evaluate proportionally between Islamic and Western education, then sorting and choosing between the two; and those which are still relevant to the times, need to be synthesized (combined) towards the ideal educational concept.On the one hand, Western education (the concept of Freire) strongly emphasizes aspects of "liberation" and "humanization" but does not touch the plain of "moral-transcendence"; on the other hand, Islamic education (Zarnuji's concept) is more likely to emphasize aspects of "moral-transcendence" and less to touch the ground of "liberation" and "humanization".From this, it means that the concept of Freire's education philosophically does not conflict with the values of Islamic teachings that do require humanization and liberation from ignorance, poverty, and underdevelopment. While Zarnuji's education, which is synthesized with Freire's education, contains moral values and a transcendental dimension. Therefore, if Zarnuji's education was combined (synthesized) with Freire's education, it would be an ideal Islamic education concept; moral-rational-based Islamic education; or Islamic education based on the spirit of the Qur'an, namely humanization, liberation, and transcendence.